Enterococcus faecalis resistant to vancomycin and teicoplanin (VanA phenotype) isolated from a bone marrow transplanted patient in Brazil - Rosangela F. Cereda; Helio S. Sader; Ronald N. Jones; Lilian Sejas; Antônia M. Machado; Yara P. Zanatta; Sinaida T. M. S. Rego; Eduardo A. S. Medeiros (Brazilian Journal of Infectious Diseases)
We report for the first time in Brazil, a patient from whom an Enterococcus faecalis VanA phenotype was isolated. Glycopeptide resistance is not commonly observed in Enterococcus faecalis, so this finding is of great concern since this species is responsible for 90% of enterococcal infections in Brazil. The isolate was recovered from a surveillance rectal swab culture from a patient with acute lymphocytic leukemia (ALL). Identification to the species level was performed by conventional biochemical tests and Vitek GPI cards. Antimicrobial susceptibility testing was evaluated by use of broth microdilution and Etest (AB BIODISK, Solna, Sweden) methods. The isolate was identified as E. faecalis and was considered resistant to both vancomycin (MIC, > 256 mug/mL) and teicoplanin (MIC, 256 mug/mL). The isolate also showed high level resistance to gentamicin and streptomycin (MICs, > 1024 mug/mL), but was considered susceptible to ampicillin (MIC, 4 mug/mL). Although the frequency of enterococcal infections is very low in most Latin America countries, the finding of glycopeptide (VanA) resistance in E. faecalis increases concern about apreading antimicrobial resistance in this region.